Penerapan Pencatatan Akuntansi Pada UMKM Gula Semut Aren Kabupaten Rejang Lebong - Arnova, Iwin; Herawati, Helmi; Sari, Selpi Nopita (Jurnal Dehasen Mengabdi, 2022)
Palm sugar SME's located in Air Meles Atas village, Selupu Rejang sub-district, have tried to carry out various breakthroughs by innovating raw materials in the form of palm sugar into ant sugar products, by creating various types of palm sugar. So it is important to keep records from raw materials to sales and profit and loss obtained by these SMEs, but have not implemented good accounting records in their business, it is necessary to conduct training on the application of accounting records for palm sugar SMEs as a solution to these problems. The training aims to provide soft skills in accounting records and increase understanding of how good accounting records should be for MSME actors. The training method is carried out with the stages of identification, preparation, training and evaluation. The result of this training is that palm sugar business actors have better skills in carrying out financial records and are able to apply them to their MSME businesses.